Employer Perceptions When Applying Criminal History Information to the Hiring Process - Levy McCanna, Karen S (2019)
In recent years, the state of Illinois has joined the ban the box movement which typically prohibits employers from inquiring about a prospective employee's criminal history until it has been determined whether the candidate meets the core qualifications for the position. Little, however, is known whether this legislative change has impacted how private employers use criminal history information and to what extent knowledge of criminal history impacts final hiring decisions. Using Kingdon's policy streams concept as a guide, the purpose of this general qualitative study was to understand whether implementation of ban the box principles impacts final hiring decisions. Data were collected through interviews with 27 hiring authorities in the state of Illinois. These data were transcribed, inductively coded, and then subjected to a thematic analysis procedure. Findings revealed that when previously convicted applicants were hired for positions, the most common reasons were noted as the quality and presentation of the candidate during the interview, possession of relevant job-related skills, and the candidate appeared remorseful of past behavior. When candidates were rejected by employers, it was most commonly because of a perceived nexus between the convicting offense and essential job requirements. Implications for positive social change include recommendations policy makers to consider future policy development that focuses on balancing the positive consequences of successful offender reentry with concern for public safety. Doing so may encourage lower recidivism and prosocial behavior including improved employment sustainability for those convicted of crimes, thereby promoting overall public safety objectives